Study of grain-level deformation and residual stresses in Ti-7Al under combined bending and tension using high energy diffraction microscopy (HEDM). (September 2016) - Chatterjee, K.; Venkataraman, A.; Garbaciak, T.; Rotella, J.; Sangid, M.D.; Beaudoin, A.J.; Kenesei, P.; Park, J-S.; Pilchak, A.L.
Graphical abstract: Abstract: In-situ high energy diffraction microscopy (HEDM) experiments are carried out to analyze the state of combined bending and tension in a Ti-7Al alloy under room temperature creep. Grain-level elastic strain tensors are evaluated from HEDM data. Atomistic calculations are used to predict elastic constants of Ti-7Al, to be used in determination of stress from strain. The stress gradient and residual stresses are successfully determined, which allows the demarcation between macro-/micro-level residual stresses. A cluster of three neighboring grains are identified that highlight the variation of mean and effective stress between grains. Crystallographic orientations and slip characteristics are analyzed for the selected grains. It is inferred that the interfaces between loaded grains with markedly different stress triaxiality and slip tendency are potential spots for material damage.